PENINGKATAN PENGETAHUAN SANTRIWATI DALAM MENJAGA KESEHATAN REPRODUKSI WANITA - Sri Rahayu; Emma Rachmawati; Mulyanti Mulyanti; Rina Yuliana Subur (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Al-Husna Islamic Boarding School, Bogor Regency, which consists of young women (santriwati) with limited health service infrastructure, there has never been a visit by local health workers who provide counseling on women's reproductive health, toilet cleanliness, food intake, hygiene behavior, and problems with femininity that are often experienced by female students. These factors in the future will become an accumulation (time bomb) of disturbances in the reproductive organs, physically and mentally in female students. The community service activity was themed "Fostering Healthy Santriwati at the Al-Husna Islamic Boarding School, Bogor Regency. The purpose of providing guidance on women's reproductive health is to increase knowledge and skills in early detection of reproductive health disorders and the practice of breast self-examination in an effort to detect early breast cancer in female students. Community-based Participatory Research (CBPR) uses community service methods with health education techniques, the practice of early detection of SADARI and early symptoms of reproductive health disorders, and the distribution of pre- and post-test questionnaires as a measure of Santriwati's understanding. The results show an increase in knowledge after being given counseling and guidance on women's reproductive health. It is hoped that Santriwati will consistently carry out early detection of BSE, recognize early symptoms of reproductive health disorders, and promote good personal hygiene to improve health